PORT DRAMA: PUBLIC EXPECTATIONS IN THE DEVELOPMENT OF SURABAYA PORT FROM 1883 TO 1930 - Muhammad Farhan Fernandi (CV. Fahr Publishing, 2025)
The development of Surabaya Port during the Dutch colonial era was a significant part of the history of maritime transportation infrastructure in Indonesia. This process involved not only technical policies but also sparked public debates involving various societal elements, including the press, engineers, trade associations, and politicians in the parliament. This study aims to discuss the public debates regarding the development of Surabaya Port during the colonial period and analyze its impact on colonial policies in Surabaya. The study employs a historical method by analyzing public debates that took place before and during the port's development. The findings indicate that there was significant support from Handelsvereeniging and Kamer van Koophandel en Nijverheid for the construction of maritime infrastructure to support the distribution of exports and imports. The Soerabaijasch Handelsblad newspaper, supported by plantation capitalists, helped publicize this issue, involving engineers and liberal politicians in the Netherlands. The conclusion of this research is that the development of the port should not be viewed solely from a technical perspective, but also influenced by pressures from private sectors seeking profits from modern infrastructure. Additionally, debates involving commercial, technical, and political aspects—engaging civil society, engineers, and politicians—ultimately shaped the direction of colonial infrastructure policies in Dutch East Indies.